Islamic Moderation Values in the Qur’an and Hadith and Their Relevance to Contemporary Social Life - Mufidah, Zulfatul (Academia Publication, 2025)
Islamic moderation values are the core of Islamic teachings that place balance, justice, and tolerance as the foundation of human life. This concept not only includes the dimension of worship, but also includes social, political, and cultural relations. Moderation in Islam teaches a balance between worldly and ukhrawi aspects, encourages respect for diversity, and rejects extremes that have the potential to divide society. In the context of the Qur'an, the concept of moderation is reflected in verses such as Surah Al-Baqarah (2:143), which describes Muslims as ummatan wasathan (middle ummah). This emphasizes the importance of being fair and balanced in all aspects of life. Meanwhile, the Hadith emphasizes the application of moderation by emphasizing the importance of avoiding excessive or fanatical attitudes in carrying out religious teachings. The application of these values in social life has become very relevant in the modern era, where society faces various challenges such as intolerance, polarization, and radicalism. Moderation serves as a middle ground that avoids extremism and exclusivism, creating a space for dialogue, cooperation, and mutual respect. Therefore, Islamic moderation is not only a theological principle but also a practical solution to build a peaceful and inclusive social order